Electron–nucleus scalar–pseudoscalar interaction in PbF: Z-vector study in the relativistic coupled-cluster framework - Sasmal, S.; Talukdar, K.; Nayak, M.K.; Vaval, N.; Pal, S. (Molecular Physics, 2017)
The scalar–pseudoscalar interaction constant of PbF in its ground state electronic configuration is calculated using the Z-vector method in the relativistic coupled-cluster framework. The precise calculated value is very important to set upper bound limit on (Formula presented.)-odd scalar–pseudoscalar interaction constant, ks, from the experimentally observed (Formula presented.)-odd frequency shift. Further, the ratio of the effective electric field to the scalar–pseudoscalar interaction constant is also calculated which is required to get an independent upper bound limit of electric dipole moment of electron, de, and ks and how these (de and ks) are interrelated is also presented here. © 2017 Informa UK Limited, trading as Taylor & Francis Group